1986
DOI: 10.1007/bf01469535
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental conditions on the steric stabilization of casein micelles

Abstract: In an attempt to characterize the steric stabilizing sheath around the casein micelles of bovine milk, photon correlation spectroscopy techniques have been used to measure the micellar radius on exposure to ethanolic buffers of varying pH, ionic strength and calcium concentration. It is shown that on exposure to alcohol, the stabilizing protein sheath undergoes dimensional collapse and that immediately prior to aggregation, a minimum or core radius is reached, characteristic of the diluting buffer conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…When higher amount of NaCl are considered, more chloride ions could bind to the protein surface so that the preferential hydration by water is overcome, leading to the observed salting-out effect. Another study 54 showed that NaCl addition to casein micelles in skim milk stabilized them against aggregation by an increase of the hairy layer but with no modification of the casein hydrodynamic radius.…”
Section: Casein Micelle Size Morphology and Repartition Associated Wmentioning
confidence: 98%
“…When higher amount of NaCl are considered, more chloride ions could bind to the protein surface so that the preferential hydration by water is overcome, leading to the observed salting-out effect. Another study 54 showed that NaCl addition to casein micelles in skim milk stabilized them against aggregation by an increase of the hairy layer but with no modification of the casein hydrodynamic radius.…”
Section: Casein Micelle Size Morphology and Repartition Associated Wmentioning
confidence: 98%
“…Variations in emulsion stability obtained with different batches of sodium caseinate can be mainly attributed to differences in their mineral contents (especially ionic calcium) [102]. In commercial practice, the production of a cream liqueur with a long shelf-life requires that the 'free' calcium ion concentration be lowered by incorporation of a chelating agent (sodium citrate) [103].…”
Section: Sodium Caseinatementioning
confidence: 99%
“…The pH of the concentrate was 6.7, Na-azide (0.2 g kg À1 ) was added to avoid bacterial growth. Following Horne and Davidson, (1986), the casein concentrate was diluted in a Ca-imidazole buffer (50 mM NaCl, 5 mM CaCl Á 6H 2 O (Prolabo), 20 mM imidazole, C 3 H 4 N 2 (Merk Darmstadt, Germany)). The pH of the buffer was adjusted to 7.0 using HCl diluted in MilliQ-water.…”
Section: Sample Preparationmentioning
confidence: 99%